Bisnis Franchise Dalam Pandangan Hukum Islam - Muhammad Erland Fauzi; Muhammad Randhika Priyatna; Andrey Naufal Arizzki; Fitri Yetty; Alfatih S. Manggabarani (IAIN Langsa, 2022)
Franchise is a business system that is currently popular with the public. Through the franchise system, doing business activities becomes easier. This is because the franchise uses a business system where the franchisor grants rights to the franchisee to be able to use or exploit intellectual property rights or inventions owned by the franchisor through an agreement. Franchise is justified according to Islamic law as long as it fulfills the pillars and conditions of the agreement, and the principles of muamalah are also fulfilled. The franchise business opens many business opportunities for the community. In the franchise business, openness, honesty and prudence are applied. Even though its presence has an impact on the small businesses around it, the competition that is created is healthy competition. The franchise business model is basically a derivative or development of the syirkah. In the franchise business scheme, the terms of the contract, such as the percentage of profit sharing, must be stated completely and clearly in an agreement based on a syirkah contract. This research uses a literature study approach. The purpose of this research is to find out the views of Islamic law regarding franchise business.